Use of complementary & alternative medicines (CAM) among cancer patients evaluating health belief of cancer patients in the context of CAM / Maryam Farooqui, Aishah Adam and Humera Naz - Farooqui, Maryam; Adam, Aishah; Naz, Humera (2012)
Cancer patients’ knowledge about cancer and experiences with the therapies including CAM plays an important role in long term adherence in their disease management. This study aimed to explore cancer patients’ knowledge about cancer and perceptions towards conventional therapies and to understand the contributing factors to their medication adherence in Malaysian population. At the same time the study also aimed to determine Malaysian cancer patients’ decision making about the use of Complementary and Alternative Medicines (CAM) in cancer management. A qualitative research approach was adopted to gain a better understanding of the current perceptions and knowledge held by cancer patients. Twenty patients were interviewed using a semi structured interview guide. Saturation point was reached after the 18th interview and no new information was emerged after the subsequent 2 interviews. All interviews were transcribed verbatim and analyzed by means of a standard content analysis framework. For the first objective a total of three themes were identified from the interview analysis Knowledge about the causes of cancer, self beliefs towards the effectiveness of conventional therapies to treat cancer, and personal self belief and experiences towards adverse effects due to conventional therapies. Most of the patients related their cancer cause as God’s will. Participants perceived conventional therapies as effective due to its scientific methods of preparations. Fear of side effects were among the reasons in delay seeking treatments, however perceptions were reported to change after getting treatments with effective management to reduce the risks of side effects. The analysis if second objective revealed four themes: conceptualizing CAM, discovery and decision making process, reasons for using or not using CAM and barriers to CAM use. Generally, the participants were most comfortable with the term traditional medicines or in local language lubat kampung’, i.e. medicines comes from ‘local traditions’. Mixed perceptions were shown towards the use of CAM to cure cancer, however, slow onset of action and cost was cited as a major barrier in CAN! use. Concerns towards the safety and efficacy of CAM for cancer as well as their potential interactions with the conventional therapies highlights the importance of patients’ knowledge towards cancer and its treatment. The study finding provides ground information about cancer patients’ perceptions towards cancer and its treatment including convetional and CAM therapies. Priorities for future research should be focus among patients who defaulted the conventional therapies at any stage. The study findings would also help in designing educational programs to enhance awareness towards cancer and its treatment among healthy individuals.